Effect of Extrinsic Cues on Perception of Private Label Quality and Customer Satisfaction - Bawa, Pardeep; Bathurutheen, Faizal (Indian Journal of Marketing, 2016)
The increasing cost of living has affected one and all in India. It has become virtually impossible to bring down the grocery and other household products’ bills. Store brands may act as a rescuer in this situation. Average store share of private labels in India isn’t high, but it is constantly increasing. The pilot study showed that customers are pretty unaware about the quality standard of private labels. This can be attributed to negligible marketing communication of private labels. Thus, this study was aimed to know whether extrinsic cues like perceived private label quality, perceived private label price, perceived store image had any impact on attitude of customers towards private labels’ quality and customer satisfaction. The results showed that perceived private label price and perceived store image, unlike perceived private label quality, positively affected attitude of customers towards private label quality, and eventually, customer satisfaction. The study might help store managers to devise strategic plans to use extrinsic cues to have a favorable perception about private labels to make customers loyal towards store and store brands.